Effect from Fluorization Upon Formation as Well as Luminescence for ZrO₂:Eu Nanogranules - Nguyen Thi Phuong Loan (Indonesian Journal of Material Research, 2026)
ZrO2:Eu phosphor materials were synthesized using a solid-state reaction method in order to investigate their structural and luminescent properties. The obtained powder samples were systematically characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and photoluminescence (PL) spectroscopy. XRD patterns of all Eu-doped samples reveal the coexistence of monoclinic and cubic phases of ZrO2, indicating that phase transformation occurs during the high-temperature solid-state synthesis process. The results further suggest that the samples undergo crystallization in a dense solid form. SEM observations confirm the formation of aggregated crystalline particles with relatively uniform morphology. At room temperature, the PL spectra of all investigated samples exhibit a broad emission band attributed to host-related luminescence, along with distinct sharp emission peaks corresponding to the characteristic radiative transitions of Eu3+ ions under optical excitation. Notably, the overall luminescence intensity of Eu3+ increases by at least six times with increasing fluorine content, demonstrating the strong influence of fluorine incorporation on the optical performance of the phosphor. Possible mechanisms responsible for the enhanced luminescence behavior, including changes in local crystal field symmetry and defect-related energy transfer processes, are discussed. These findings highlight the potential of ZrO2:Eu materials for photonic and luminescent applications.